Clinical implications of p53 alterations in oral cancer progression: a review from India - Patel, K.R.; Vajaria, B.N.; Singh, R.D.; Begum, R.; Patel, P.S. (Experimental Oncology, 2018)
p53 plays a central role in prevention of normal cell from the development of the malignant phenotype. Somatic alterations (mutations, loss of heterozygosity, deletions) in p53 are a hallmark of most human cancers and cause defects in normal p53 function. However, in the tumors harboring wild-type p53, there are alterations in the regulation of the p53. Thus, understanding why p53 is unable to perform its role as a tumor suppressor in these wild-type tumors is very crucial. Germ-line polymorphisms in p53 are also anticipated to cause measurable disturbance in p53 function. Over-expression as well as polymorphic variants of MDM2 might have effects on cancer development. In addition, degradation of p53 by E6 protein of high risk human papillomavirus is also suggested as one of the mechanisms which attenuate p53 responses in oral carcinogenesis. p53 has also been demonstrated to mediate cellular responses upon various DNA damaging cancer therapies, importantly, apoptosis. These responses have been implicated in an individual’s ability to respond to these cancer therapies. Thus, exploring mechanisms by which normal function of p53 is affected in the comprehensive way in oral cancer might aid in the identification of tumor characteristics, prognosis and thus in the development of a new approach to treat the oral cancer.